In vitro Propagation of Singgalang Cabbage (Brassica oleracea var. capitata L.) on Murashige and Skoog Modification Media for Preservation Purpose - Sari, Maya; Idris, Muhammad (Jurnal Biologi Tropis, 2024)
Singgalang Cabbage is one of the local cabbage cultivated on the foothills of Mount Singgalang, West Sumatra. Recently, the existence of this cabbage has decreased, so conservation and preservation efforts need to be carried out. This research was conducted to develop method for in vitro propagation and preservation of singgalang cabbage. The Murashige and Skoog (MS) were used as basal media with two experimental stages, i.e., shoot initiation with 6-Benzylaminopurine (BAP), and root induction and plantlet preservation with modification of MS media. The nodal and shoots were used as explants. The results showed that increment of BAP concentrations gave a significant effect on shoot initiation after 60 days of treatment. MS media-enriched with BAP 2 mg/L gave significant increment of shoots (4 shoots/nodus) and leaves (11.67) numbers when compared to other treatments. For root induction and plantlet preservation, it was found that the earlier of root formation was observed in modification of MS media at ½ and ¼ strength. Meanwhile, MS media at ⅛ strength was observed to be better media for plant height increment (4.75 cm) when compared to other treatments. It was found that the plantlets survived and grew well after 120 days under in vitro condition.